"Effective" Requesting: A Scoping Review of the Literature on Asking Families to Consent to Organ and Tissue Donation. (May 2017) - Chandler, Jennifer A.; Connors, Matthew; Holland, Giles; Shemie, Sam D.
Abstract : Background: Families are often asked to consent to the donation of their deceased relative's organs or tissues. These end-of-life conversations are important because they affect consent rates as well as the psychological impact of the decision for families. This scoping review of the literature on requesting family consent was prepared to support of the development of leading practice recommendations for end-of-life conversations with families of potential donors. A scoping review maps research activity in a field across a range of commentary and empirical study designs but does not attempt meta-synthesis of empirical data or quality assessment. Methods: We performed a scoping review of the peer-reviewed literature from January 2000 to February 2015 on the questions of what constitutes an "effective" request and the factors that affect consent rates and family satisfaction with their decision and the process. This review includes a final set of 168 articles addressing (a) whether, when, and how to ask families for consent to donation or (b) characteristics of families or decedents that affect families' decisions or family satisfaction with their decisions. Results: Six main themes were identified: (1) the objectives of requesting and encouraging family consent to donation, (2) the effect of the donation decision on family well-being, (3) the process of requesting family consent, (4) the impact of the quality of the care for the deceased and for the family, (5) the content and manner of the request for family consent, and (6) the characteristics of the family and deceased that affect the request for family consent. Conclusion: This scoping review found that there is a large literature on how to modify the process and manner of the request to increase family consent rates. Another important line of inquiry focuses on the psychological impact of the decision on the family. Although a scoping review does not attempt to synthesize results or draw evidence-based conclusions, the literature generally supports the intuitive expectations that compassionate and respectful care for the deceased and family, listening for and addressing family concerns, and an attitude to donation that is positive (but not solely procurement-focused) and is best for both consent rates and family well-being. Although the presumption is often that the primary objective of asking for family consent is to secure consent and donation, some ethical commentary on requesting consent emphasizes that this objective must be balanced with the parallel obligation to protect the psychological well-being of families. This places some constraints on the approaches used in family consent discussions. Abstract : Supplemental digital content is available in the text.